Increased risk of incident dementia following use of anticholinergic agents: A systematic literature review and meta‐analysis. Issue 1 (23rd October 2020) - Dmochowski, Roger R.; Thai, Sydney; Iglay, Kristy; Enemchukwu, Ekene; Tee, Silvia; Varano, Susann; Girman, Cynthia; Radican, Larry; Mudd, Paul N.; Poole, Charles
Abstract: Background/rationale: Long‐term treatment with anticholinergic agents may increase the risk of cognitive impairment or dementia. This systematic literature review and meta‐analysis aimed to assess the impact of ≥3 months of exposure to anticholinergics as a class on the risk of dementia, mild cognitive impairment, and change in cognitive function. The impact of anticholinergic agents specifically used to treat overactive bladder was also evaluated. Materials and Methods: A systematic literature review was conducted to identify English language articles evaluating the impact of anticholinergic use for ≥3 months on dementia or cognitive function in adult patients. Databases searched included PubMed, Embase, and the Cochrane Library. Meta‐analyses were conducted using random‐effects models; 95% confidence intervals (CIs) and 95% prediction intervals (PIs) were reported. Results: A total of 2122 records were identified. Out of those, 21 studies underwent qualitative synthesis and 6 reported endpoints relevant for inclusion in a meta‐analysis assessing the risk of incident dementia. The overall rate ratio for incident dementia was 1.46 (95% CI: 1.17–1.81; 95% PI: 0.70–3.04; n  = 6). The risk of incident dementia increased with increasing exposure ( n  = 3). In addition, two studies from the meta‐analysis reported an increased risk of dementia with ≥3 months of use of bladder antimuscarinics (adjusted odds ratios ranged from 1.21 to 1.65, depending on exposure category). Conclusion: Anticholinergic use for ≥3 months increased the risk of dementia on average by an estimated 46% versus nonuse. This relationship was consistent in studies assessing overactive bladder medications. The risk of developing dementia should be carefully considered in the context of potential benefit before prescribing anticholinergics.